Chapter L’inquieto diritto del lavoro. Rileggendo il siddhartiano Riccardo Del Punta - ROSELLI, ORLANDO (Firenze University Press, 2025)
The restless Riccardo Del Punta was culturally and scientifically resistant to ideological simplifications. This was due to his refined culture, not only in legal matters, which made him a scholar of labor law capable of engaging with the complexity of postmodern social transformations. A jurist of 360 degrees, he questioned law as a legal dimension, a product not only of legislative provisions but of overall cultural and social processes. His scholarly and teaching commitment represents a testamentary legacy in the tradition of titans such as Gino Giugni, Otto Kahn-Freund, Marco Biagi, and Massimo D’Antona.